2022
DOI: 10.1371/journal.pone.0263303
|View full text |Cite
|
Sign up to set email alerts
|

Absence of association between host genetic mutations in the ORAI1 gene and COVID-19 fatality

Abstract: The calcium ion channel ORAI1 has emerged as a promising therapeutic target for the Coronavirus Disease 19 (COVID-19)-associated pneumonia, and a pharmacological inhibitor of ORAI1 has now reached clinical trials for severe COVID-19 pneumonia. Whether ORAI1 itself is associated with an increased risk for severe COVID-19 presentation is still unknown. Here, we employed genetic association analysis to investigate the potential association of host genetic polymorphisms of ORAI1 with the risk of Severe Acute Respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, the calcium ion channel gene ORAI1 is known for its role in immune response, inflammation, platelet activation and thrombus formation, and was therefore considered as a potential drug target for COVID-19. However, a UK Biobank study found that genetic variants within ORAI1 were not associated with severe COVID-19 (Shawer et al, 2022) consistent with observational analyses that found no association between calcium channel blocker use and COVID-19 outcomes (Alsagaff et al, 2021). Other analyses using UK Biobank data have reported that the ApoE e4/e4 genotype (which not only affects lipoprotein function but also moderates macrophage inflammatory phenotypes) increases the risk of severe COVID-19, independently of pre-existing dementia, cardiovascular disease and type 2 diabetes (Kuo et al, 2020).…”
Section: Study Enhancements To Enable Covid-19 Researchmentioning
confidence: 99%
“…For example, the calcium ion channel gene ORAI1 is known for its role in immune response, inflammation, platelet activation and thrombus formation, and was therefore considered as a potential drug target for COVID-19. However, a UK Biobank study found that genetic variants within ORAI1 were not associated with severe COVID-19 (Shawer et al, 2022) consistent with observational analyses that found no association between calcium channel blocker use and COVID-19 outcomes (Alsagaff et al, 2021). Other analyses using UK Biobank data have reported that the ApoE e4/e4 genotype (which not only affects lipoprotein function but also moderates macrophage inflammatory phenotypes) increases the risk of severe COVID-19, independently of pre-existing dementia, cardiovascular disease and type 2 diabetes (Kuo et al, 2020).…”
Section: Study Enhancements To Enable Covid-19 Researchmentioning
confidence: 99%